Clinical Radiology Case Presentation: Do’s and Don’ts - Punnen, Geethu E.; Keshava, Shyamkumar N.; Gibikote, Sridhar (Indian Journal of Radiology and Imaging, 2021)
Clinical case presentation is part of daily routine for doctors to communicate with each other to facilitate learning, and ultimately patient management. Hence, the art of good clinical case presentation is a skill that needs to be mastered. Case presentations are a part of most undergraduate and postgraduate training programs aimed at nurturing oratory and presentation design skills. This article is an attempt at providing a trainee in radiology a guideline to good case presentation skills.
Keywords: clinical case presentation; presentation skills; clinical radiology case presentation; resident training